Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/md.0000000000025340
|View full text |Cite
|
Sign up to set email alerts
|

What are the predictors for recurrence of Crohn's disease after surgery?

Abstract: Surgical resection is an unavoidable part of the current treatment options for Crohn's disease (CD), and more than half of patients develop recurrence. The aim of this study was to investigate the predictors for recurrence in the long-term follow-up of CD patients after surgery. Medical records of consecutive CD patients who were operated on between January 2003 and January 2015 were retrospectively analyzed. Data including demographic and clinical characteristics of the patients were recorded. Recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 52 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Regarding the penetrating disease, Ozgur et al retrospectively reported an association between penetrating behavior (p = 0.011), intra-abdominal abscess (p = 0.040) and postoperative disease recurrence [43]. A subsequent meta-analysis of six RCTs reproduced these results.…”
Section: Disease Characteristicsmentioning
confidence: 91%
“…Regarding the penetrating disease, Ozgur et al retrospectively reported an association between penetrating behavior (p = 0.011), intra-abdominal abscess (p = 0.040) and postoperative disease recurrence [43]. A subsequent meta-analysis of six RCTs reproduced these results.…”
Section: Disease Characteristicsmentioning
confidence: 91%
“…High post‐operative recurrence rates have encouraged multiple studies to attempt to identify specific patterns of disease which predict recurrence 7 . Identified risk factors for post‐operative disease recurrence include disease location, surgical indication, 8,9 age, disease phenotype, 10 colonic and perianal involvement, 11,12 urgent operation and post‐operative steroid use 13 …”
Section: Introductionmentioning
confidence: 99%